Education and Social Inequality - Tamara Kusimova (Journal of Economic Sociology, 2016)
The XVII April International Academic Conference on Economic and Social Development was held from April 19 to 22, 2016, at the National Research University Higher School of Economics in Moscow with support of the World Bank. For the first time, the issue of education opportunities were discussed in a separate section on the Role of Education in the Reproduction and Reduction of Social Inequalities. The topic brought together Russian, British, Chinese, American, and European scholars. Over three days, the section hosted thematic sessions, presentations of applied and theoretical research, and panel discussions. Discussions highlighted several main aspects, including comparative cross-national research on the effects of educational opportunities, social policy, studies of informal education, and further research.The keynote speakers of the section were C. Aedo (World Bank), D. Alexandrov (HSE), A. Asmolov (FIRO), P. Bianchi (University of Ferrara), M. Carnoy (Stanford University), M. Feuer (The George Washington University), I. Froumin (HSE), L. Gortazar (World Bank), M. Jackson (Stanford University), N. Karmaeva (HSE), D. Konstantinovskiy (Institute of Sociology of the Russian Academy of Sciences), S. Kosaretsky (HSE), B. Kupriyanov (HSE), H. Levin (Columbia University), R. Murnane (Harvard Graduate School of Education), E. Pavlenko (HSE), A. Sidorkin (HSE), D. Semenov (HSE), V. Sobkin (Russian Academy of Education), K. Szafraniec (Nicolaus Copernicus University), A. Zakharov (HSE).